Pengembangan Instrumen Pengukuran Kepuasan Pasien atas Layanan Pharmaceutical Care - TUNGGUL ADI PURWONUGROHO; VITIS VINI FERA RATNA UTAMI; NURYANTI NURYANTI (Fakultas Farmasi Universitas Pancasila, 2015)
Development and validation of the instrument to assess patient satisfaction to pharmaceutical care is important to be conducted. It will provide a reliable tool so that research to measure patient satisfaction regarding to pharmaceutical care could be further developed. First, content of the questionnaire was developed based on the literature review and focus group discussion of the panel. Then, the draft was tested to 5 respondents as a readability measurement. After received input from readability test’s respondents and made some changes, panel re-tested the questionnaire as content validity analysis. Finally, the questionnaire was distributed to other 30 respondents to get data for factor analysis, construct validity test and reliability test. Thirteen items was found as important factors that inuence patient satisfaction to pharmaceutical care based on literature review and focus group discussion activity. The questionnaire was further tested on 30 respondents. In the factor analysis assessment, categorization of items could not be made. Validation test using Pearson correlation and reliability test using Cronbach’s Alpha toward each item on the questionnaire showed that all items were valid and reliable, except one item in the “hope” section. Further study with greater number of respondents is required to re-validate this questionnaire.